Penerapan Handout Berbasis Pendekatan Sets (Science, Environment, Technology, And Society) pada Materi Bioteknologi Terhadap Hasil Belajar Siswa MAS Darul Ihsan Aceh Besar - Eliyanti Eliyanti; Hasanuddin Hasanuddin; Mudatsir Mudatsir (Universitas Islam Negeri Ar-Raniry, 2018)
A research to investigate the improvement of student learning outcomes on Biotechnology concept with the application of SETS (Science, Environment, Technology and Society) based handout has been carried out at MAS DarulIhsan Aceh Besar on the second semester of the Academic Year 2017/2018. The research used The Pre-experimental with One Group Pretest-Posttest Design. The samples were 32 students of class XII/b MAS Darul Ihsan Aceh Besar. The data were collected by using multiple choice questions. The results showed that student learning outcomes were increased after the implementation of handout based on SETS. It can be concluded that the application of handout that is based on SETS approach can improve students learning outcomes on Biotechnology concept in MAS Darul Ihsan Aceh Besar.